Islamic economics : a book of readings - Karwai, Sulaiman A.; Habib, Aisha G.; Jibril, Binta Tijjani; International Institute of Islamic Thought. Nigeria Office (London : Routledge, 2019)
In its pursuit to equip the reader with a basic knowledge of Islamic economics, this book divulges the micro-foundations of the discipline, and highlights the predominant schools of thought that exist in the field. It explains, in simple terms, what Islamic economics entails and how it can be studied as a science in relation to the Holy Quran, the Sunnah and the Islamic intellectual tradition based on these two sources. The book familiarizes the reader with knowledge of the basic maxims of the discipline. It then establishes the arguments that are presented by the proponents of religion-based economics, specifically Islam, and apprises readers about the aforementioned schools as they exist. A number of chapters consider the dimension of the dilemmas the discipline is facing, and the chronological progress of the field is reviewed, hence providing a comprehensive overview of the topic. The book deals with the issues about the origins of Islamic economics, the basic methodological questions, the use of the opportunities offered by fiqh in the methodological discussions and the main problems arising from the encounter with other cultures and civilizations. It offers practical solutions, despite the differing schools of thought, not unlike the development of conventional Economics where radical differences between Keynesian, Classical and Monetarist approaches existed. It concludes by incorporating some of the finest works that explain to the reader how Islamic economics may progress as a discipline. This guide will provide both students and researchers in Comparative Economic Studies, Islamic Economics and Islamic Finance with an essential overview of the field.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Banks & Banking; BUSINESS & ECONOMICS / Business Ethics; Economics -- Religious aspects -- Islam; Islam -- Economic aspects; Finance -- Religious aspects -- Islam; Finance, Personal -- Religious aspects -- Islam